An Important Aspect of Satisfaction on Mobile Apps: An Usability Evaluation Based on Gender - Dessy G. Palyama; Golda Tomasila (PT Mattawang Mediatama Solution, 2022)
The quality of the feasibility of a mobile application can be measured by evaluating the usability using certain testing methods. The refore to improve the performance of mobile applications, it is necessary to measure the level of satisfaction and user acceptance of the application. This study aims to improve the quality of the Myelkomsel mobile application by measuring the level of satisfaction and acceptance of end-users and evaluating the relationship between the level of user satisfaction with user gender differences using the System Usability Scale (SUS) method. Data collection was carried out by distributing questionnaires to 46 Telkomsel provider users consisting of 22 male users and 24 female users. The results showed that the average SUS score was 71.96 for the whole user. According to the calculation of the level of user acceptance included in the category of Acceptable, the scale of the class level is included in category C, and the ranking is included in the good category. While the results of calculations from the SUS Percentile Rank Score show that the MyTelkomsel mobile application is in class C. There are no significant differences according to gender, the average SUS score of the male is 71.93, and female is 71.98 so that gender differences do not affect the level of satisfaction and acceptance application. It can be seen that the level of end-user satisfaction from the MyTelkomsel mobile application is good but still has possible problems with its use